Effects of the Vertebral Artery Ostium/Subclavian Artery Angle on In-Stent Restenosis after Vertebral Artery Ostium Stenting. (28th April 2021) - Su, Hui; Yu, Shengyuan; Tian, Chenglin; Du, Zhihua; Liu, Xinfeng; Wang, Jun; Cao, Xiangyu
Abstract : Background and Purpose . The cause of in-stent restenosis (ISR) after vertebral artery ostium (VAO) stenting remains unclear. We evaluated factors associated with ISR in patients who underwent VAO stenting. We also assessed the feasibility of stenting for treating VAO stenosis (VAOS). Methods . Between January 2016 and October 2018, sixty-four consecutive patients who underwent a total of 66 stenting procedures were screened for symptomatic and asymptomatic atherosclerotic VAOS. Of these patients, 57 had complete follow-up data. The baseline patient demographics and morphological features of the VAO were recorded. Potential factors influencing ISR, including conventional cerebrovascular disease risk factors, were assessed, together with outcome events including recurrent transient ischemic attack (TIA), stroke, and vascular-related mortality. Results . The average follow-up period was 13.2 ± 4.6 months. Technical success was achieved in all interventions. The degree of stenosis was reduced from 77.2 ± 6.1 % to 13.7 ± 8.9 % after the procedure. ISR was detected in eight treated vessels (14.0%) and occlusion in two (5.3%) arteries. Of the 57 patients, one had an ischemic stroke and 5 had TIAs. The angle of the VAO at the subclavian artery was associated with the risk of restenosis (preoperative, P = 0.04 ; postoperative, P = 0.02 ). Conclusions . Stenting is a feasible and effective treatment for VAOS. The angle of the VAO at the subclavian artery may contribute to the development of ISR.